Incidence of Carbapenem-Resistant Gram-Negative Bacterial Infections in Critically Ill Patients with COVID-19 as Compared to Non-COVID-19 Patients: A Prospective Case-Control Study - Diamanto Aretha; Sotiria Rizopoulou; Leonidia Leonidou; Sotiria Kefala; Vasilios Karamouzos; Maria Lagadinou; Anastasia Spiliopoulou; Markos Marangos; Fotini Fligou; Fevronia Kolonitsiou; Fotini Paliogianni; Stelios F. Assimakopoulos (Critical Care Research and Practice)
Introduction. Critically ill COVID-19 patients hospitalized in intensive care units (ICU) are immunosuppressed due to SARSCoV-2-related immunological effects and are administered immunomodulatory drugs. This study aimed to determine whether these patients carry an increased risk of multi-drug resistant (MDR) and especially carbapenem-resistant Gram-negative (CRGN) bacterial infections compared to other critically ill patients without COVID-19. Materials and Methods. A prospective case-control study was conducted between January 2022 and August 2023. The ICU patients were divided into two groups (COVID-19 and non-COVID-19). Differences in the incidence of CRGN infections from Klebsiella pneumoniae, Acinetobacter spp., and Pseudomonas aeruginosa were investigated. In addition, an indicator of the infection rate of the patients during their ICU stay was calculated. Factors independently related to mortality risk were studied. Results. Forty-two COVID-19 and 36 non-COVID-19 patients were analyzed. There was no statistically significant difference in the incidence of CRGN between COVID-19 and non-COVID-19 patients. The infection rate was similar in the two groups. Regarding the aetiological agents of CRGN infections, Pseudomonas aeruginosa was significantly more common in non-COVID-19 patients (p=0.007). COVID-19 patients had longer hospitalisation before ICU admission (p=0.003) and shorter ICU length of stay (LOS) (p=0.005). ICU COVID-19 patients had significantly higher mortality (p<0.001) and sequential organ failure assessment (SOFA) score (p<0.001) compared to non-COVID-19 patients. Μortality secondary to CRGN infections was also higher in COVID-19 patients compared to non-COVID-19 patients (p=0.033). Male gender, age, ICU LOS, and hospital LOS before ICU admission were independent risk factors for developing CRGN infections. Independent risk factors for patients’ mortality were COVID-19 infection, obesity, SOFA score, total number of comorbidities, WBC count, and CRP, but not infection from CRGN pathogens. Conclusions. The incidence of CRGN infections in critically ill COVID-19 patients is not different from that of non-COVID-19 ICU patients. The higher mortality of COVID-19 patients in the ICU is associated with higher disease severity scores, a higher incidence of obesity, and multiple underlying comorbidities, but not with CRGN infections.